Alcohol interventions, alcohol policy and intimate partner violence: a systematic review - Wilson, I.; Graham, Kathryn; Taft, A. (BioMed Central Ltd, 2014)
Background: Intimate partner violence (IPV) is a significant global public health issue. The consistent evidence thatalcohol use by one or both partners contributes to the risk and severity of IPV suggests that interventions thatreduce alcohol consumption may also reduce IPV. This study sought to review the evidence for effects on IPV ofalcohol interventions at the population, community, relationship and individual levels using the World HealthOrganization ecological framework for violence.Methods: Eleven databases including Medline, PsycINFO, CINAHL and EMBASE were searched for English-languagestudies and grey literature published 1 January 1992 – 1 March 2013 investigating whether alcohol interventions/policies were associated with IPV reduction within adult (=18) intimate relationships. Eleven studies meeting designcriteria for attributing effects to the intervention and ten studies showing mediation of alcohol consumption wereincluded in the review. The heterogeneity of study designs precluded quantitative meta analysis; therefore, a criticalnarrative approach was used.Results: Population-level pricing and taxation studies found weak or no evidence for alcohol price changesinfluencing IPV. Studies of community-level policies or interventions (e.g., hours of sale, alcohol outlet density)showed weak evidence of an association with IPV. Couples-based and individual alcohol treatment studies found arelationship between reductions in alcohol consumption and reductions in IPV but their designs precludedattributing changes to treatment. Randomized controlled trials of combined alcohol and violence treatmentprograms found some positive effects of brief alcohol intervention as an adjunct to batterer treatment forhazardous drinking IPV perpetrators, and of brief interventions with non-dependent younger populations, buteffects were often not sustained.Conclusions: Despite evidence associating problematic alcohol use with IPV, the potential for alcohol interventionsto reduce IPV has not been adequately tested, possibly because studies have not focused on those most at risk ofalcohol-related IPV. Research using rigorous designs should target young adult populations among whom IPV anddrinking is highly prevalent. Combining alcohol and IPV intervention/policy approaches at the population,community, relationship and individual-level may provide the best opportunity for effective intervention.